Comparison of inflammatory mediator cytokine responses to inactivated virus platform COVID-19 vaccines between elderly and young adult populations - Hayati, Taureni; Kartinah, Neng T.; Wibowo, Heri; Purwoko, Reza Y. (Narra Sains Indonesia, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has encouraged global vaccine research, yet vaccine effectiveness in the elderly remains a concern due to immunosenescence. The aim of this study was to compare the cytokine response elicited by an inactivated virus-based COVID-19 vaccine between elderly and young adults, focusing on key cytokines involved in cellular and humoral immunity: tumor necrosis factor-alpha (TNF-α), interleukin (IL)-2, IL-6, IL-10, and interferon-gamma (IFN-γ). A cross-sectional study was conducted in the Jakarta-Bogor region of Indonesia from January 2023 to December 2023. The study population was divided into two age cohorts: elderly (60−85 years) and younger adults (30−40 years). Blood samples were collected twice, after the first booster dose and four weeks after the second booster dose. Serum cytokine concentrations were measured using Luminex assays with microparticles conjugated to monoclonal antibodies against TNF-α, IL-2, IL-6, IL-10, and IFN-γ. Comparisons of the cytokine levels were conducted using Student’s t-tests or Mann-Whitney U tests as appropriate. A total of 74 individuals were included, with 37 each in the elderly and young adult groups. The results showed significant differences in cytokine responses between the two age groups. After the first booster, the levels of IL-6 and IFN-γ were significantly higher in young adults compared to the elderly. After the second booster, the levels of IL-6 were still significantly higher in the young adult group compared to the elderly group (p=0.001). Data indicated that after the second booster dose, the levels of TNF-α increased significantly in the young adult group only (p=0.004), while the levels of IL-2 (p=0.040) and IFN-γ (p=0.006) increased in the elderly group only compared to after the first dose. IL-10 levels increased in both groups (both had p=0.020). This study highlights that young adults had stronger pro-inflammatory responses, while the elderly relied more on IL-2 and IFN-γ for T-cell immunity, suggesting the need for vaccination strategies for the elderly to optimize immune responses.